The "silent" noise: moving forward from bias to noise in football referees` decision-making - Samuel, R. D.; Galily, Y.; Hochman, G. (International Journal of Sport and Exercise Psychology, 2025)
In football, referees are expected to deliver consistent and unbiased judgments, grounded in professional knowledge and expertise. However, much of the research on referees` decision-making has traditionally focused on the concept of "bias" in their judgments. This review shifts attention to referees` decision-making noise - defined as "undesirable variability in judgments of the same problem" (Kahneman, D., Sibony, O., & Sunstein, C. R. [2021]. Noise: A flaw in human judgment (p. 40). Little, Brown Spark). Noise reflects the inconsistency in referees` responses to similar match situations, resulting in diverse decisions for comparable infringements. The article is structured into five key sections. First, we introduce the concept of noise in human judgment. Second, we explore the issue of noise in the context of football refereeing, offering examples and relevant data. Particular emphasis is placed on noise in foul decisions, incorporating both raw data and findings from existing literature. A detailed framework is presented, outlining the components, sources, detection methods, and strategies for reducing judgment noise in refereeing. In the third section, we compare bias and noise in football officiating, examining potential mechanisms underlying each. The fourth section considers strategies for reducing errors in refereeing and discusses the potential costs associated with implementing such measures. Finally, we argue why stakeholders in football officiating should expand their focus beyond bias to address the implications of noise in refereeing decisions.